2002
DOI: 10.1007/s003800200049
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of a uterine leiomyoma extending through the inferior vena cava into the right heart

Abstract: We present a case of a 38-year-old woman with intravenous leiomyomatosis originating from the uterus involving the right ventricle, right atrium, inferior vena cava, and iliac veins. Tumors in the heart and the inferior vena cava were removed using cardiopulmonary bypass and circulatory arrest; 10 days after the cardiac operation, hysteroadnexectomy was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…These include the following: (1) the tumors in cardiac chambers are oval (mostly) or serpentine in appearance, with well‐demarcated borders and homo‐ or hetero‐echogenic texture; (2) the size of intracardiac masses is variable and most are relatively large (37 mm in the mean diameter) and mobile when detected; (3) intracardiac tumors always locate in right heart and having extended from the IVC; (4) no mass has stalk; (5) IVL with intracardiac extension may cross the tricuspid valve into right ventricle, right ventricle outflow tract and pulmonary arterial bed resulting in pulmonary emblism. These echocardiographic characteristics have not been analyzed previously in a group of patients, but they are consistent with some published case descriptions 7,10–13 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These include the following: (1) the tumors in cardiac chambers are oval (mostly) or serpentine in appearance, with well‐demarcated borders and homo‐ or hetero‐echogenic texture; (2) the size of intracardiac masses is variable and most are relatively large (37 mm in the mean diameter) and mobile when detected; (3) intracardiac tumors always locate in right heart and having extended from the IVC; (4) no mass has stalk; (5) IVL with intracardiac extension may cross the tricuspid valve into right ventricle, right ventricle outflow tract and pulmonary arterial bed resulting in pulmonary emblism. These echocardiographic characteristics have not been analyzed previously in a group of patients, but they are consistent with some published case descriptions 7,10–13 …”
Section: Discussionsupporting
confidence: 88%
“…These echocardiographic characteristics have not been analyzed previously in a group of patients, but they are consistent with some published case descriptions. 7,[10][11][12][13] The echocardiographic well-demarcated and inhomogeneous appearance of the tumor is easily understood combined with the pathological findings. Microscopically, the intravascular tumors are composed of mitotically inactive spindle cells devoid of cytologic atypia and are surrounded by endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…One-stage operations also have many shortcomings, however, including longer operation time, increased trauma, more bleeding, and more postoperative complications. 11,16 In our group, the three cases of one-stage surgery were successful, but the blood loss was relatively more (Fig 2).…”
Section: Discussionmentioning
confidence: 55%
“…1 Invasion of pelvic veins and vena cava by leiomyoma and its possible extension to right cardiac chambers may cause a variable spectrum of symptoms, ranging from sudden death, cardiac tamponade, dyspnea, tachycardia, and arrhythmias, to abdominal pelvic pressure or abnormal bleeding, edema of the inferior limbs, or even Budd-Chiari syndrome. 11 One of the following circumstances should be taken into account for the possibility of the diagnosis of IVL:…”
Section: Discussionmentioning
confidence: 99%
“…For recent 10 years, the literature contains more reports of IVL, fewer than 100 cases with cardiac involvement [2] . Harris reported that 64% of patients with IVL had a history of hysterectomy, diagnosed after 4 years [3] .…”
Section: Discussionmentioning
confidence: 99%